Staging depth : Eugene O'Neill and the politics of psychological discourse - Pfister, Joel (University of North Carolina Press, 1995)
Pfister examines the history of the middle-class family and of Freudian pop psychology in the 1910's and 1920's to reconstruct the cultural conditions for the imagining and popularizing of "depth", a trope that was central to O'Neill's dramatic vision
Keywords: O'Neill, Eugene, -- 1888-1953 -- Knowledge -- Psychology.; O'Neill, Eugene, -- 1888-1953 -- Et la psychologie.; O'Neill, Eugene, -- 1888-1953; O'Neill, Eugene, -- (1888-1953) -- Critique et interprétation.; O'Neill, Eugene, -- (1888-1953) -- Pensée politique et sociale.; O'Neill, Eugene, -- (1888-1953) -- Psychologie.; O'Neill, Eugene.; Literature and society -- United States -- History -- 20th century.; Domestic drama, American -- History and criticism.; Drama -- Psychological aspects.; Middle class in literature.; Psychology in literature.; Families in literature.; Littérature et société -- États-Unis -- Histoire -- 20e siècle.; Théâtre bourgeois américain -- Histoire et critique.; Classes moyennes dans la littérature.; Psychologie dans la littérature.; Familles dans la littérature.; Théâtre (Genre littéraire) -- Aspect psychologique.; DRAMA -- American.; Domestic drama, American; Drama -- Psychological aspects; Families in literature; Literature and society; Middle class in literature; Psychology; Psychology in literature; United States; Psychologie; Literatur; Cultuurverandering.; Verenigde Staten.; Historisch kritische methode.; Literatuursociologie.; Middenklassen.; Literatuurpsychologie.; Psychologie -- Dans la littérature.; Classes moyennes -- Dans la littérature.; Famille -- Dans la littérature.; Literature and society -- United States -- 20th century.; 1900-1999; Electronic books.; Criticism, interpretation, etc.; History